2016
DOI: 10.1021/acsami.6b12481
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Dual PEGylation of Inorganic Porous Nanocarriers for Extremely Long Blood Circulation in Vivo

Abstract: Drug carrier systems based on mesoporous inorganic nanoparticles generally face the problem of fast clearance from bloodstream thus failing in passive and active targeting to cancer tissue. To address this problem, a specific dual PEGylation (DPEG) method for mesoporous silicon (PSi) was developed and studied in vitro and in vivo. The DPEG coating changed significantly the behavior of the nanoparticles in vivo, increasing the circulation half-life from 1 to 241 min. Furthermore, accumulation of the coated part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 44 publications
(75 reference statements)
2
39
0
Order By: Relevance
“…It has been well demonstrated that the density and length of PEG, as well as its mixed heterogeneous layer structure, could affect blood circulation. 5,28 It has also been reported that the increase in molecular weight of PEG can prolong the circulation time of PEG in blood. 29 For example, when the molecular weight increased from 6,000 to 19,000, the half-life time could be increased from 18 minutes to 1 hour in blood.…”
Section: Effects Of Core Size and Peg Layer On The Clearance Rate Of mentioning
confidence: 98%
See 1 more Smart Citation
“…It has been well demonstrated that the density and length of PEG, as well as its mixed heterogeneous layer structure, could affect blood circulation. 5,28 It has also been reported that the increase in molecular weight of PEG can prolong the circulation time of PEG in blood. 29 For example, when the molecular weight increased from 6,000 to 19,000, the half-life time could be increased from 18 minutes to 1 hour in blood.…”
Section: Effects Of Core Size and Peg Layer On The Clearance Rate Of mentioning
confidence: 98%
“…Similar to gold NPs and porous silicon NPs, they are required to undergo surface modification to avoid quick clearance by the immune system prior to arriving at the predesignated organs. 4,5 Recent studies in this field revealed that the blood circulation of IONPs can be controlled by their particle size, morphology, and surface ligands. 6,7 Since spherical IONPs have been widely adopted for biomedical applications, including the commercial Endorem (Guerbet S.A., Roissy Charles de Gaulle Cedex, France), and Sinerem (AMAG Pharmaceuticals, Inc., Cambridge, MA, USA), the effect of core size and surface ligands on circulation time has attracted extensive attention.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification which makes magnetic particles stable in physiological conditions is highly researched area since particle aggregation can make treatment ineffective or can cause negative health effects. Myriads of magnetic particle preparation and functionalization procedures were reported, however only two types of particles entered clinical trials, i.e., particles coated with polysaccharides or silica [ 234 , 235 ]. Further, polymeric compounds are highly investigated to hide magnetic particles from the immune system.…”
Section: Magnetic Nanoparticles In the Real Worldmentioning
confidence: 99%
“…1316 Furthermore, polydisperse PEG brushes of varying length have been shown to be more effective than monodisperse PEG layers in reducing protein adsorption, 17, 18 indicating the design may generate long circulating NPs. 19 The improvement was attributed to the increased PEG density and layer thickness because short PEG chains fit in between longer PEG molecules, and steric repulsions between grafted chains increase the overall thickness of the PEG layer. However, some studies have reported the existence of an optimal density of grafted PEG for repelling proteins.…”
mentioning
confidence: 99%